PERBEDAAN PENILAIAN KEPALA SEKOLAH DAN PENILAIAN DIRI SENDIRI TERHADAP KOMPETENSI PEDAGOGIK GURU PRODUKTIF DI SMKN 1 PARIAMAN - 60-65 . Ira Safitri (CIVED, 2013)
The purpose of this research is to show the assessment of the headmaster and self assessment about pedagogic competence at SMK Negeri 1 Pariaman. The kind of this research is descriptive quantitative research. The data research taken by use research scale model questioner for self assessment and interview to get the headmaster. The data research was taken in 3 steps, they are: (1) the descriptive data, (2) Analysis test regulation, (3) hypothesis testing. To process the testing data research is by using the SPSS program in 16,0 version. The result of this research show the both of the mean are the differentiate with the assessment (t) is 7,606 and probability assessment is 0,008<0,05. Then, Ho get the push away and Ha is received. The hypothesis find the differentiate  between the headmaster assessment and self assessment in productive teacher pedagogic competence at SMK N 1 Pariaman. Key words :        assessment, competence, pedagogic, productive teacher